2008
DOI: 10.1177/039463200802100333
|View full text |Cite
|
Sign up to set email alerts
|

Extragenital Lichen Sclerosus and Atrophicus Treated with Topical Steroids and Retinoids in a Child with Vitiligo

Abstract: Lichen sclerosus and atrophicus (LSA) most commonly affects the anogenital region. Extragenital involvement is rare, and women are reported to be affected 6 to 10 times more often than men. The aetiology of LSA is unclear, but genetic, physiological and environmental factors are thought to be involved. Several lines of evidence support the hypothesis of an autoimmune basis for LSA; an increased incidence of tissue-specific antibodies and an association with autoimmune disorders such as vitiligo, alopecia areat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Lichen sclerosus (LS) is a chronic inflammatory dermatosis that predominantly affects the anogenital region in prepubertal girls and postmenopausal women. 1 Extragenital involvement of LS is uncommon, but more often seen in the latter population and classically involves the upper trunk, axillae, buttocks, and lateral thighs. Lesions typically present as porcelain-white atrophic plaques, similar to genital lesions, often with follicular plugging and areas of ecchymosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lichen sclerosus (LS) is a chronic inflammatory dermatosis that predominantly affects the anogenital region in prepubertal girls and postmenopausal women. 1 Extragenital involvement of LS is uncommon, but more often seen in the latter population and classically involves the upper trunk, axillae, buttocks, and lateral thighs. Lesions typically present as porcelain-white atrophic plaques, similar to genital lesions, often with follicular plugging and areas of ecchymosis.…”
Section: Discussionmentioning
confidence: 99%
“…Especially the existence of bullous lesions in extragenital LS is rare and has been reported infrequently [9]. Extragenital bullous lesions are generally asymptomatic and localized.…”
Section: Discussionmentioning
confidence: 99%
“…The association of vitiligo with a variety of autoimmune diseases has already been described, and findings have suggested that the immune system might be involved in killing melanocytes [26]. In fact, vitiligo is usually associated with a 2- to 10-fold increase in auto-antibodies against numerous organs, particularly the thyroid and gastric parietal glands and adrenals [27].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence support the hypothesis of an autoimmune basis for scleroatrophic lichen, such as an increased incidence of tissue-specific antibodies and an association with autoimmune disorders such as vitiligo, alopecia areata and thyroid disease [26]. …”
Section: Discussionmentioning
confidence: 99%